2020
DOI: 10.5001/omj.2020.64
|View full text |Cite
|
Sign up to set email alerts
|

Infectious Complications Reporting in Common Variable Immunodeficiency: A Systematic Review and Meta-analysis

Abstract: Objectives Common variable immunodeficiency (CVID) is a heterogeneous disorder characterized by hypogammaglobulinemia and increased susceptibility to recurrent infections. Methods We searched PubMed, Web of Science, and Scopus databases to find eligible studies from the earliest available date to January 2018 with standard keywords. Pooled estimates of the infection prevalence and the corresponding 95% confidence intervals were calculated using random-effects models. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 89 publications
(33 reference statements)
0
10
0
1
Order By: Relevance
“…They become more infected with bacterial pathogens due to impaired humoral immunity. In contrast, fungal and viral pathogens are less common in them, as they are more likely to infect people with cellular immunodeficiency (8). The case presented also had a history of UC, and the drugs mentioned for its treatment cause impairment of cellular immunity.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…They become more infected with bacterial pathogens due to impaired humoral immunity. In contrast, fungal and viral pathogens are less common in them, as they are more likely to infect people with cellular immunodeficiency (8). The case presented also had a history of UC, and the drugs mentioned for its treatment cause impairment of cellular immunity.…”
Section: Discussionmentioning
confidence: 97%
“…They become more infected with bacterial pathogens due to impaired humoral immunity. In contrast, fungal and viral pathogens are less common in them, as they are more likely to infect people with cellular immunodeficiency ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a systematic review including a large cohort of CVID patients, infection pattern and frequency together with predominating immune response abnormalities have been analyzed [ 42 ]. The reported findings demonstrated that in CVID children, comparably to adults, pneumonia was the most prevalent infection, assessed in as much as 73% of pediatric patients, and it was followed by upper respiratory tract infections, such as otitis media, pharyngitis, and tonsillitis as occurring in 65%, and gastrointestinal infections in 44% of them.…”
Section: Infections and Infectious Complicationsmentioning
confidence: 99%
“…In single patients, other severe infectious episodes, such as osteomyelitis [ 4 , 13 ], septic arthritis [ 43 ], central nervous system (CNS) infections [ 43 , 44 ], and sepsis [ 4 , 13 , 45 ], were reported. Bacterial etiologies were noted most frequently, in 41.7% of infectious episodes compared to viral, parasitic, or fungal infections, assessed in 25.4%, 18.8%, and 3.4%, respectively [ 42 ]. Interestingly, a higher rate of pneumonia was inversely proportional to the patients’ age, and as respiratory tract infections are the leading clinical indicator of pediatric CVID, they contributed significantly to an early diagnosis of the disease [ 42 ].…”
Section: Infections and Infectious Complicationsmentioning
confidence: 99%
See 1 more Smart Citation